The dark side of diversification: The case of US financial holding companies - Stiroh, Kevin J.; Rumble, Adrienne (Journal of Banking & Finance, 2006)
Potential diversification benefits are one reason why US financial holding companies are offering a growing range of financial services. This paper examines whether the observed shift toward activities that generate fees, trading revenue, and other non-interest income has improved the performance of US financial holding companies (FHCs) from 1997 to 2002. We find evidence that diversification benefits exist between FHCs, but these gains are offset by the increased exposure to non-interest activities, which are much more volatile but not necessarily more profitable than interest-generating activities. Within FHCs, however, marginal increases in revenue diversification are not associated with better performance, while marginal increases in non-interest income are still associated with lower risk-adjusted profits. The key finding that diversification gains are more than offset by the costs of increased exposure to volatile activities represents the dark side of the search for diversification benefits and has implications for supervisors, managers, investors, and borrowers.